(untitled) (European Journal of Pure and Applied Mathematics, 2026)
A sixth-order family of three-point multiple root solvers with polynomial and rational weight functions are investigated by means of Möbius conjugacy map applied to a prototype polynomial of the form (z-p)^m (z-q)^m with the related parameter spaces and dynamical planes. The interesting dynamics is shown through various stability surfaces and parameter spaces including dynamical planes.